2020
DOI: 10.21467/ajgr.9.1.1-13
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Performance of Briquette Made from Millet Bran: A Neural Network Approach

Abstract: Millet bran possesses good fuel quality and can be successfully used as a professional feedstock for producing solid biofuel.  In this paper, a framework for developing an Artificial Neural Network (ANN) to estimate the performance of millet bran briquettes is presented by using experimental data to train, test, and validate the ANN. With the capacity of the developed multi-layer ANN, the effects of moisture content, temperature, and applied pressure on the density, durability, and impact resistance are predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…ANNs are trained by frequently exploring the most suitable relationship between the input and target (output) values which help in creating a model after a sufficient number of learning repetitions, or training known as epochs. 22 Figure 5 represents the coefficient of correlation (R) values for best ANN models from each group (single and double hidden layers). R-value (as shown in Equation ( 5)) is used to measure the extent of correlation between the actual and predicted value.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ANNs are trained by frequently exploring the most suitable relationship between the input and target (output) values which help in creating a model after a sufficient number of learning repetitions, or training known as epochs. 22 Figure 5 represents the coefficient of correlation (R) values for best ANN models from each group (single and double hidden layers). R-value (as shown in Equation ( 5)) is used to measure the extent of correlation between the actual and predicted value.…”
Section: Resultsmentioning
confidence: 99%
“…It is well reported in several studies that TANSIG–PURELIN combination demonstrated better adaptation to the ANN. 22,26,27 Demonstration of the ANN prediction is done in Table 2. The actual activity values are converted to normalized value to get a better standard comparison.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the large amount of millet grown, millet husk a by-product is gotten in large quantities. There are nine species of millet in the world, according to [16], with a total production of 28.38 million tons, of which 11.36 million tons (40 %) were produced in Africa. Nigeria produces about 40% of Africa's millet (4.53 tons, with the northern part of the country producing more than 80% of the millet [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, these layers interface is that the different portion of the "craftsmanship" of engineering systems to resolve the complicated issues of the real world. therefore, neural systems, with their a lot of grounded capability to derive which means from diffi cult or inexact information, are often utilized to disengage styles and observe trends that are additionally complicated to be taken note by either folks or different laptop procedure[7][8][9][10][11].the topology diagrams shown, every arrow represents an association between 2 neurons and indicates the pathway for the fl ow of knowledge. Every association encompasses a weight, Associate in nursing the whole number that controls the signal between the 2 neurons.…”
mentioning
confidence: 99%